2010
DOI: 10.1002/chem.201002340
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic and Aliphatic CH Hydrogen Bonds Fight for Chloride while Competing Alongside Ion Pairing within Triazolophanes

Abstract: Triazolophanes are used as the venue to compete an aliphatic propylene CH hydrogen-bond donor against an aromatic phenylene one. Longer aliphatic C-H...Cl(-) hydrogen bonds were calculated from the location of the chloride within the propylene-based triazolophane. The gas-phase energetics of chloride binding (ΔG(bind) , ΔH(bind) , ΔS(bind) ) and the configurational entropy (ΔS(config) ) were computed by taking all low-energy conformations into account. Comparison between the phenylene- and propylene-based tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 100 publications
7
78
1
Order By: Relevance
“…Similarly, prior work with triazolophane macrocycles showed only four low-lying, semi-planar conformations. 14 These macrocycles clearly follow the structural definition of shape-persistence by displaying little conformational freedom. In these cases, shape persistence is self-evident.…”
Section: Introductionmentioning
confidence: 82%
“…Similarly, prior work with triazolophane macrocycles showed only four low-lying, semi-planar conformations. 14 These macrocycles clearly follow the structural definition of shape-persistence by displaying little conformational freedom. In these cases, shape persistence is self-evident.…”
Section: Introductionmentioning
confidence: 82%
“…In a separate manuscript, Flood and co-workers have used the triazolophane scaffold to compare the strength of aromatic and aliphatic C-H hydrogen bond donors by replacing one of the phenylene groups in receptor 62 with a propylene linker in receptor 65. 45 Gas phase computational studies showed that the length of the CHÁ Á ÁCl distance in the propylene based triazophane 65 was greater for the aliphatic (3.02 Å) than the aromatic (2.96 Å) CH donor, supporting its classification as a weaker interaction. The gas phase studies also suggested that the free energy of binding decreased from À194 to À182 kJ mol…”
Section: Anion Receptors Containing Ch Hydrogen Bond Donorsmentioning
confidence: 95%
“…In addition, the benzene ring of the Schiff base ligand and the pyridine ring of the Schiff base ligand were twisted, at an angle of 55.25°with respect to each other. Intermolecular C-HÁ Á ÁCl interaction also has been reported in several recent literature sources [35,36]. Whilst exploring the acting forces in the crystal lattice, we discovered that there exist C-HÁ Á ÁCl weak interactions: C11-H11Á Á ÁCl1 i = 2.876 Å; C2-H2Á Á ÁCl2 ii = 2.876 Å.…”
Section: Structures Of Complexes 1-4mentioning
confidence: 67%